Effectiveness of Cognitive Behavior Therapy in Reduction of Academic Stress and Enhancement of Academic Performance in University Students - Maria Ashraf, Uzma Masroor & Mussarrat Jabeen Khan (Pakistan Journal of Psychology, 2020)
Academic stress among the students of university remained an issue that hinders their academic performance despite adequate efforts. The present study investigated the effectiveness of Cognitive Behavior Therapy (CBT) for academic stress and academic performance in university students. The research was based upon multiple case study design and the sample consisted of total 30 students with the average age range of 19 to 30 years. The Academic Stress Scale (ASS) by Kohn and Frazer 1986 was used to scrutinize subjects with higher level of stress while the academic performance was obtained from their grades from last two semesters. The selected sample was administered with the psychological treatment by utilizing two techniques of CBT (Imaginal exposure and cognitive restructuring) with 10 sessions per subject. The results of paired sample t-test showed the reduction in academic stress and an enhancement in academic performance at post-test. The study has implications and suggest future research direction